Design and synthesis of N1, N8-diacetylspermidine analogues having a linker with desired functional groups. Issue 4 (10th January 2019) - Ohta, Reiya; Oguro, Akihiro; Nishimura, Kazuhiro; Murai, Kenichi; Fujioka, Hiromichi; Arisawa, Mitsuhiro
Abstract : The synthesis of new N 1, N 8 -diacetylspermidine (DiAcSpd) analogues having a linker with desired functional groups in the methylene skeleton, which have been designed by theoretical calculations, is described. Abstract : The synthesis of new N 1, N 8 -diacetylspermidine (DiAcSpd) analogues having a linker with desired functional groups in the methylene skeleton, which have been designed by theoretical calculations, is described. We have also achieved the preparation of DiAcSpd supported on solid-phase resins, which have the potential to be used for the evolution of ligands by exponential enrichment (SELEX).